Komunikasi Pembangunan di Media Sosial sebagai Social Problem Solving Masyarakat Pamulang - Putri, Maulidina Wamareta; Subagyo, Mutiara Fathiyah; Inayah, Syafina Nur (PT Literasi Nusantara Publisher, 2024)
Social problems are social phenomena with various dimensions. In general, social problems are usually explained as conditions that no one wants, because these conditions and expectations do not meet the applicable specifications. The problem is how the diversity of social institutions can synergize so that they can contribute to Social Welfare Development, through social media. goal, Realization of a productive and effective Social Institution Network in handling social welfare problems Strengthening the role and function of social institutions in handling social welfare problems by developing a social institution network. The research method carried out by researchers uses descriptive research with literature studies or literature studies. Social Institutions are systems that become a vehicle that allows members of society to interact according to patterns or systems of behaviour and relationships that are responsible for activities to meet special needs in community life. Philosophical assumptions of the role of social institutions in the pamulang environment Philosophical assumptions to build guidance and counselling as a science based on the assumptions of ontology, epistemology, axiology, methodology and rhetoric.